The Process of Finding Meaning of Life in Young Offender - Sri Hesti D.K Kardipranoto; Dian Lestari Anakaka; Juliana Marlin Y Benu (Universitas Nusa Cendana, 2021)
Correctional Students can find meaning in life even though they have to be imprisoned. A person can change his life to be more meaningful through five stages, namely the stage of suffering, the stage of self-acceptance, the stage of finding the meaning of life, the stage of meaning realization, and the stage of a meaningful life. The purpose of this study was to describe the process of finding the meaning of adolescent life at Lembaga Pembinaan Khusus Anak Klas I Kupang. This research is qualitative research with descriptive methods. Participants in this study were three people who were selected by purposive sampling method with the characteristics of having served a prison term of more than two years. The results showed that the three participants were at a meaningful life stage where Erman, Yoga, and Carlos interpreted their lives in prison with gratitude for their experiences while in detention.